THE IMPACT OF PRODUCT DIFFERENTIATION STRATEGY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY AT ENHAI SOERABI BANDUNG RESTAURANT - Ullya Rahmi Aswin; Danny Hidayat; Fatma Ariani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study investigates the impact of product differentiation strategies and customer satisfaction on customer loyalty at Enhai Soerabi Bandung Restaurant in Padang. Using a sample of 130 respondents, the research explores the influence of three dimensions of product differentiation—service offering differentiation, service delivery differentiation, and image differentiation—on customer satisfaction and loyalty. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 2.0. The results show that both service offering differentiation and image differentiation significantly affect customer satisfaction, while service delivery differentiation did not have a significant impact. Furthermore, customer satisfaction was found to have a strong positive effect on customer loyalty. The findings suggest that Enhai Soerabi Bandung should focus on enhancing its service offerings and brand image to foster customer satisfaction and loyalty. The study also highlights the importance of maintaining high-quality service delivery but recognizes that factors like food quality and pricing also contribute to customer loyalty. Limitations of the study include its focus on a single restaurant and a relatively small sample size. Future research should explore these factors across different locations and with larger samples to generalize the findings further .